Regional Economic Outlook, October 2018, Sub-Saharan Africa : Capital Flows and The Future of Work. (International Monetary Fund, 2018)
The macroeconomic outlook for sub-Saharan Africa continues to strengthen with higher growth, easing inflation, and stabilizing public debt ratios with some countries improving their fiscal balances. But there are concerns on the quality of the fiscal adjustment and underlying vulnerabilities have yet to be decisively addressed.